Acompanhamento de crianças e adolescentes com história familiar de hipertenção arterial - Chaves, Emília Soares (2007)
The presence of alterations of blood pression in children and adolescents has shown that arterial hypertension may have its initial history in this life stage. It is believed that the harmful effects of hypertension, when they exist, could be minimized if their presence was detected precociously, if the evaluation of blood pressure was done periodically and if it were a mandatory part of the consultations to children and adolescents. Epidemiologic studies about blood pressure in childhood also reveal that the persistence of high values in this stage of life reinforces the idea that hypertension in adulthood is a direct result of hypertension in childhood. One aimed to follow children and adolescents with family history of arterial hypertension for a long time, analyzing the evolution of percentage/classification of blood pressure in children and adolescents. The longitudinal/prospective study was developed in a poor community of Fortaleza-Ceará. The blood pressure was evaluated in five meetings: first semester of 2004; first semester of 2005; second semester of 2005; first semester of 2006 and second semester of 2006. The data collection was conducted at home in pre-determined periods. By the data obtained, it was possible to confirm that children and adolescents can have high blood pressure, even without an specific cause and no sinthomatology. The group presented was composed by 141 participants, in the majority females (71). The ages varied from 6 to 21 years old in the period of accompaniment. The highest values of blood pressure were found in the male patients. A bigger percentage of the children and adolescents were relatives of second degree of arterial hypertension bearers (48.9%), and these showed the biggest average values of SBP and DBP. Out of 92 children, 30 remained with no alterations of the percentages of blood pressure in all evaluations; 42 presented alterations starting from the 3rd evaluation; eight showed alterations of the percentage only on the last evaluation conducted; 11 showed alterations of the percentages of blood pressure in all the evaluations and 20 presented alterations of the percentages in some evaluation, but in the last one showed normal percentage of blood pressure. Out of 49 adolescents, 32 remained with no alterations of the percentages of blood pressure in all evaluations; eight presented alterations starting from the 3rd evaluation; two individuals showed alterations of the percentages only on the last evaluation; six presented alterations of the percentages of blood pressure in all the evaluations and three presented alterations of percentages in some evaluation, but in the last one presented normal blood pressure percentage. It was not possible to identify statistic significance concerning the risk factors presented during the accompaniment, apparently being the family factor the biggest contribution to the high values of blood pressure. It is confirmed the necessity of a regular monitoring of children and adolescents’ blood pressure and, even without significant statistic correlation, the precocious identification of risk factors such as overweight, obesity, sedentarism, positive history to hypertension, smoking and drinking in the prevention of future cardiovascular events.